Kearifan Lokal Islami Masyarakat Jawa: Mengupas Nilai Tasawuf dalam Tradisi Nyadran - Nur Laily, Laily; Nashiruddin, Nashiruddin (PUTIH: Jurnal Pengetahuan Tentang Ilmu dan Hikmah, 2021)
Indonesia's diversity includes religion, ethnicity, tradition, and culture. Various traditions carried out by society circle. Nyadran’s tradition is one of example form local wisdom that still preserved by javanese people. This tradition proven to be in multiple regions toward month of Ramadan, the ritual widely carried out. Nyadran underwent acculturation process in the Walisongo era, from Hindu-Buddhist culture to islamic traditions. However, the appearance of  sense conservatism in society make minder thinking to preserve the nation's culture. Nyadran is considered out from Islamic religion and impressed heretics. This research aims to remove the understanding of conservatism and inferiority among society by discussing the values of Sufism contained in the nyadran’s tradition. The practice form of these values can be seen from concrete of social Sufism in society, aslo their closeness to God. This research form of qualitative research with a literary approach. The author found, in nyadran’s practice, not only social dimensions with human, and nature, but also with God. This dynamic is very appropriate as a method of missionary endeavor and the development of Sufism as one of the vehicles to create the intimacy of life. Through this approach, Walisongo be able to change the practice of Sufism that nuance mystical change with Islamic and rational version. The form of this tradition still same as the beginning, but prayers are replaced with the phrase tayibah, tahlil, tahmid, and others.